customer satisfaction, customer relationship management, Fuzzy Delphi, system dynamics. - Habib A. Mirghafoori; Ali Morovati Sharifabadi; Ensiyeh Taki (تحقیقات بازار یابی نوین, 2016)
This paper investigates the factors which are affecting customers satisfaction of Mobarake steel complex . Since there is a wide rang of factors affecting customer satisfaction,this paper pays attention to those factors which have CRM approach. The investigation society of the research is the marketing experts of Moabarake steel complex who have direct relationship with customers.At first, the factors were identified by experts using Fuzzy Delphi method and then the relationship between factors were specified by cause and effect diagram (system dynamics). At the end, by use of cause and effect diagram, experts viewpoints and literature review of the study, the flow diagram was prepared. The following, some loops are explained. After that, two scenarios including the impact of increase in credit sales and also reducing the delay in shipment which are suggested by Mobarake steel complex are analyzed by use of flow diagram and Vensim soft ware.As a conclusion the paper proposes some suggestions to Mobarake steel company in order to improve its customer satisfaction.